The Value of Aspiration Cytology in Cystic Lesions of the Maxillofacial Region - Baykul, Timucin; Colok, Gulumser; Gunhan, Omer (European Journal of Dentistry, 2010)
Objectives: The majority of the pathologic structures which are seen in the oral and maxillofacial region are either cystic or tend to show cystic changes. They may have not specific clinical and radiographic findings. Therefore, it is difficult to differentiate these lesions preoperatively. For this purpose, in this research, the value of fine-needle aspiration cytology (FNAC) in preoperative diagnosis was investigated by comparing with the postoperative histopathologic diagnosis.Methods: One hundred aspirates from cystic lesions in the oral and maxillofacial region were included in this study. All of the samples except one were examined histopathologically and the results were compared.Results: The results of the FNAC specimens obtained from 100 lesions were compared with histopathologic diagnosis of these lesions. According to these results, 12 insufficient (12%), 7 positive (7%), 81 negative (81%) specimens were obtained. Among these 88 lesions, 69 of them were diagnosed specifically by cytological examination (78.4%). 62 of the 69 specific diagnoses achieved by cytological examination were confirmed histopathologically (89.85%). The histological types of the seven lesions were missed by cytological examination. There were not any complications related with the fineneedle aspiration procedure in the research.Conclusions: According to these results, the value of fine-needle aspiration biopsy in cystic lesions of the maxillofacial region is found as successful as in the solid lesions. (Eur J Dent 2010;4:1-5)
Keywords: Aspiration biopsy; Cystic; Fine-needle; Oral; Maxillofacial; Preoperative